Following the story: narrative mapping as a mobile method for tracking and interrogating spatial narratives. Issue 1 (2nd January 2019) - Hanna, Stephen P.; Carter, Perry L.; Potter, Amy E.; Bright, Candace Forbes; Alderman, Derek A.; Modlin, E. Arnold; Butler, David L.
ABSTRACT: Museums and heritage tourism sites are highly curated places of memory work whose function is the assembling and ordering of space and narrative to contour visitors' experiences of the past. Variations in such experiences within and between sites, however, necessitates a method that: (1) captures how guides, visitors, and exhibits interact within spaces when representing and performing history and (2) allows researchers to document those variations. We developed narrative mapping, a mobile and geographically sensitive form of participant observation, to enable museum scholars and professionals to systematically capture, visualize, and interpret tendencies and variations in the content, affective qualities, and spatial arrangements of museum narratives over multiple sites and across multiple tours at the same site. Two antebellum plantation museum case studies, Laura Plantation in Louisiana and Virginia's Berkeley Plantation, demonstrate the method's utility in documenting how stories are spatially configured and materially enlivened in order to analyze the ways enslaved persons are placed within these narratives.